2009
DOI: 10.2337/db08-1187
|View full text |Cite
|
Sign up to set email alerts
|

TCF7L2 Regulates Late Events in Insulin Secretion From Pancreatic Islet β-Cells

Abstract: OBJECTIVEPolymorphisms in the human TCF7L2 gene are associated with reduced insulin secretion and an increased risk of type 2 diabetes. However, the mechanisms by which TCF7L2 affect insulin secretion are still unclear. We define the effects of TCF7L2 expression level on mature β-cell function and suggest a potential mechanism for its actions.RESEARCH DESIGN AND METHODSTCF7L2 expression in rodent islets and β-cell lines was altered using RNAi or adenoviral transduction. β-Cell gene profiles were measured by qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
181
1
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 188 publications
(199 citation statements)
references
References 45 publications
(53 reference statements)
13
181
1
3
Order By: Relevance
“…In addition, Tcf7l2 knockdown reduced the expression of Munc18-1 (also known as Stxbp1) and increased the expression of Stx1a (which encodes syntaxin 1a), both of which encode key players in the control of insulin exocytosis. Interestingly both Munc18-1 and Stx1a contain a putative TCF7L2 binding site in their 5' untranslated regions, suggesting a direct regulatory role of TCF7L2 [13]. It should be noted, however, that levels of TCF7L2 mRNA [10] and TCF7L2 protein [15] are increased, not decreased, in human islets from type 2 diabetic donors.…”
Section: Tcf7l2 Incretins and The Beta Cellmentioning
confidence: 91%
See 3 more Smart Citations
“…In addition, Tcf7l2 knockdown reduced the expression of Munc18-1 (also known as Stxbp1) and increased the expression of Stx1a (which encodes syntaxin 1a), both of which encode key players in the control of insulin exocytosis. Interestingly both Munc18-1 and Stx1a contain a putative TCF7L2 binding site in their 5' untranslated regions, suggesting a direct regulatory role of TCF7L2 [13]. It should be noted, however, that levels of TCF7L2 mRNA [10] and TCF7L2 protein [15] are increased, not decreased, in human islets from type 2 diabetic donors.…”
Section: Tcf7l2 Incretins and The Beta Cellmentioning
confidence: 91%
“…• Decreased beta cell mass Decreased beta cell proliferation following TCF7L2 knockdown [12] Decreased 'maximal' insulin secretion-response to arginine at 28 mmol/l glucose [10] • Impaired insulin processing or release Altered SLC30A8, Munc18-1 and Stx1A expression in mice with Tcf7l2 knockdown [13] Increased proinsulin:insulin ratio in rs7903146 T allele carriers [9,17] Decreased 'maximal' insulin secretion-response to arginine at 28 mmol/l glucose [10] • Impaired GLP1 signalling in beta cells [9,11] Response to GLP1 impaired to greater extent than that to i.v. glucose [10] • Decreased glucagon secretion reducing beta cell insulin secretion [9] Needs replicating…”
Section: Mechanisms Whereby Altered Tcf7l2 Production or Function Maymentioning
confidence: 99%
See 2 more Smart Citations
“…Subsequent studies implicated β-cell dysfunction as the underlying cause of diabetes in patients with the TCF7L2 risk variant [2][3][4][5] and have suggested that Wnt signalling plays an important role in both pancreatic development and in the function of mature pancreatic islets [6]. The activation of the canonical Wnt pathway, by ligands such as Wnt3a, has been of particular interest as it can increase β-cell proliferation, decrease apoptosis and improve glucose stimulated insulin secretion [6][7][8][9][10][11][12]. However there is now increasing evidence that non-canonical Wnt ligands such as Wnt4 can antagonise the signalling mediated by Wnt3a and may play an equally important role in β-cell function [13][14][15].…”
Section: Introductionmentioning
confidence: 99%